The INFLUENCE OF SOCIAL MEDIA MARKETING, ONLINE CUSTOMER REVIEW, AND PRICE ON PUCHASE INTENTION IN DIGITAL CREATIVE SKILLS CLASS ON INSTAGRAM IN GENERATION Z OF JAMBI CITY - Nurhidayat, Prasetyo; Ade Octavia; Novita Sari (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
The purpose of this study was to test and analyse social media marketing, online customer reviews, and price on the purchase intention of Digital Creative Skill classes on Instagram in Generation Z Jambi City. Data was collected using a questionnaire consisting of 17 statements. The population in this study was Instagram users who knew about the Digital Creative Skill class among Generation Z in Jambi City, with a research sample size of 96 respondents and a sampling technique using purposive sampling. The analysis method used in this research is multiple linear regression analysis. The results of the study show that social media marketing, online customer reviews, and price partially and simultaneously have a positive and significant effect on purchase intention in the Digital Creative Skill class. It was found that the price variable in this study is the most dominant variable influencing purchase intention in the Digital Creative Skill class